Soluble interleukin-2 receptors, antineutrophil cytoplasmic antibodies, and other autoantibodies in patients with ulcerative colitis. Issue 5 (May 1993) - Dalekos, G N; Manoussakis, M N; Goussia, A C; Tsianos, E V; Moutsopoulos, H M
Abstract : Ulcerative colitis (UC) is an inflammatory bowel disease of unknown aetiology. In this study, serum samples from 80 patients with UC were studied for the presence of various autoantibodies and soluble interleukin-2 receptor molecules (sIL-2Rs) in an attempt to determine the degree of activation of the immune system in this disease process. Autoantibodies detected included rheumatoid factors (in 5% of patients), antinuclear antibodies (in 51.3%), anti-Ro(SSA) (in 1.3%), anticardiolipin antibodies (IgG and/or IgM classes in 26.3%), anti-double stranded DNA (IgG or IgM classes in 45%), and antineutrophil cytoplasmic antibodies (ANCAs, in 30%). The ANCAs had a perinuclear pattern (p-ANCA) in 95.8%, without anti-myeloperoxidase activity, at least in an enzyme linked immunosorbent assay (ELISA) system. Raised concentrations of sIL-2R were found in 32.5% of patients (26/80, 18 with active and eight with inactive UC). The mean (SD) sIL-2R concentrations were significantly higher in patients with active UC (595 (219) u/ml v 406 (162) u/ml, p = 0.0001) and in patients with ANCAs (584 (177) u/ml in ANCA positive v 447 (212) u/ml in ANCA negative patients, p < 0.01). The sIL-2R concentrations were correlated with increased serum concentrations of C3c (r = 0.23, p < 0.05) or C4 (r = 0.4, p < 0.001) components of the complement system and erythrocyte sedimentation rate (ESR, r = 0.44, p = 0.0001). Platelets, ESR, and C3c were not associated with disease activity (p = 0.06, 0.33 and 0.86) whereas mean (SD) serum concentrations of C4 were higher in active disease (37.4 (11.9) mg/dl v 32.3 (10.3) mg/dl, p < 0.05). The sIL-2Rs had 53% sensitivity and 82.6% specificity for disease activity whereas platelet counts had 53% sensitivity and 58.7% specificity. To conclude, UC is accompanied by an autoimmune response that results in the production of several autoantibodies and cellular immune activation, as shown by the high sIL-2R concentration, is also present. The identification of the target antigen(s) of p-ANCA would possibly act as an indicator of disease activity if this distinct subset of ANCAs can be attributed to the pathogenesis of UC. The sIL-2R concentrations seem to be a useful laboratory marker for assessing activity of the disease.